Podpapo de pesquisador: criando, implementando e avaliando um podcast de divulgação científica em Química - Silva Neto, Antonio Rodrigues da (Universidade Federal de São Carlos, 2025)
RESEARCHER'S CHAT: CREATING, IMPLEMENTING, AND EVALUATING A SCIENCE COMMUNICATION PODCAST ABOUT CHEMISTRY. Science communication plays a fundamental role in universities and society mediation, especially in the context of misinformation and disconnect between scientific production and the general public. Communicating science requires more than just transmitting data; it demands dialogue, empathy, and the recognition of the public as an active participant in the communicative process. The advancement of digital technologies and the consolidation of social networks, such as Instagram, TikTok, YouTube, and streaming platforms like Spotify, have transformed how knowledge is shared and consumed. In this scenario, the podcast stands out as a strategic tool for science communication, due to its accessible language and potential to reach different audiences. The objective of this project is to develop, implement, and evaluate the podcast "Researcher's Chat," with the aim of promoting the dissemination of scientific knowledge in the field of Chemistry. In the first stage, a survey of national scientific podcast production was conducted, based on a mixed-methods approach and data collected from Spotify, websites, and digital libraries. In the second stage, interviews were conducted with producers of science communication podcasts, analyzed according to the content analysis methodology proposed by Bardin (2011). The third stage comprised the production and analysis of the podcast PodPapo de Pesquisador, focused on science communication in Chemistry, using Spotify metrics—such as reach, retention, age range, and geographic location of the audience—in addition to monitoring the social networks Instagram and TikTok. The overall picture showed an expanding ecosystem of scientific podcasts, highlighting productions such as Scicast, Fronteiras da Ciência, Oxigênio, Chutando a Escada, and Dragões de Garagem. However, the underrepresentation of women in production teams was observed, reflecting structural imbalances still present in this field. The interviews indicated that the personal and educational trajectories of the producers significantly influence how they understand and practice science communication. The absence of multidisciplinary teams, the overload of functions, and the lack of technical training were identified as obstacles to the quality and sustainability of the projects. It was also noted that characterizing the audience is difficult, as it is still largely concentrated in profiles close to the academic environment. In the specific case of Chemistry, it was found that episodes that integrated personal narratives, life stories, and scientific content showed greater retention and engagement, while those focused only on the technical aspect obtained lower performance. Clarity in decoding information and a balance between rigor and accessibility proved fundamental to communicative success. Dissemination strategies on social media were essential to broaden reach and understand audience engagement patterns. It is concluded that, by combining language, narrative, and technique, the podcast consolidates itself as an effective means to transform scientific dissemination into effective social practice, strengthening the relationship between the knowledge produced and the public that benefits from it.
Researcher's chat: creating, implementing, and evaluating a science communication podcast about Chemistry
Keywords: Divulgação científica; Química; Podcast; Ciência; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 4. Educação de Qualidade